Improving Understanding of Short Story Content Using Learning Model Word Square in Class IV Students of SD Negeri 69 Ambon - Ribka. L. Ririhena; Anggar Purwanty Idris (Peneliti.net, 2022)
The purpose of the research is to increase the understanding of short story content in Grade IV students at SD Negeri 69 Ambon. This study applies the Classroom Action Research (CAR) method. Based on the results and discussion in this study, it can be concluded that through the Word Square can improve the ability to understand the contents of short stories in class IV SD Negeri 69 Ambon. This is based on the test results for each cycle, namely in the first cycle students obtained the minimum completeness criteria (KKM) 65 by 5 students with a percentage of 64.8% Meanwhile, in Cycle II, there was an increase of 81.90%, that is, to 100% with 9 students getting a score of 65